2021
DOI: 10.3390/jof7121052
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Sesquiterpenoids from the Edible Mushroom Craterellus odoratus

Abstract: The aim of this work was to comprehensively understand the chemical constituents of the edible mushroom Craterellus ordoratus and their bioactivity. A chemical investigation on this mushroom led to the isolation of 23 sesquiterpenoids including eighteen previously undescribed bergamotane sesquiterpenes, craterodoratins A–R (1–18), and one new victoxinine derivative, craterodoratin S (19). The new structures were elucidated by detailed interpretation of spectrometric data, theoretical nuclear magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Finally, the structure of compound 1 was established. It was named craterodoratin T after the name given in our previous work [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the structure of compound 1 was established. It was named craterodoratin T after the name given in our previous work [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nutritional and biochemical analysis studies showed that a good amount of proteins, carbohydrates, reducing and non-reducing sugars, phenolics, flavonoids, β-carotene, and lycopene were found in the fresh fruiting bodies of C. odoratus [ 9 ]. Our previous studies on the secondary metabolites of C. odoratus have reported a series of polyketides, meroterpenes, and bergamotane-type sesquiterpenes [ 10 , 11 , 12 , 13 , 14 ]. Of them, craterellin B is a merosesquiterpenoid that showed significant inhibitory activity against the isozyme of human 11β-hydroxysteroid dehydrogenases (11β-HSD1), with an IC 50 value of 3.5 μ g/mL [ 10 ], while craterellin C is also a merosesquiterpenoid from C. odoratus that showed inhibitory activities against two isozymes of human 11β-HSD1 and 11β-HSD2, with IC 50 values of 14.8 and 25.4 μ g/mL, respectively [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] To fully explore the secondary metabolites of this strain, we studied the isolation and structure characterization of A. sydowii derived from deep-sea sediments. Two pairs of new bisabolanetype sesquiterpenoids, (+)-aspersydowin A (7S) [(+)-1], (À )aspersydowin A (7R) [(À )-1], (+)-aspersydowin B (7S,11S) [(+)-2], (À )-aspersydowin B (7R,11R) [(À )-2], together with six known compounds (3)(4)(5)(6)(7)(8) were obtained. The absolute configurations of compounds 1 and 2 were ascertained by their experimental electronic circular dichroism (ECD) spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Bisabolane-type sesquiterpenoids have been reported in some fungi, such as Didiscus sp., [1][2][3] Arenochalina sp., [4] Epipolasis sp., [5] and Myrmekioderma sp. [6] Some of bisabolane-type sesquiterpenoids exhibited diverse structural features with a wide range of bioactivities, including immunosuppressive, [7,8] antiatherosclerotic [9] and anti-inflammatory activities. [10] The fungus Aspergillus sydowii is a rich source of structurally diverse natural products with a variety of biological properties, such as cytotoxicity, [11][12][13][14] antitumor, [15][16][17] antibacterial, [18] and anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%